Faster, more accurate, more confident? An exploratory experiment on soccer referees’ yellow card decision-making - Wang, Hongbiao; Zhang, Chenping; Ji, Zhiguang; Li, Xiawen; Wang, Liyan (Frontiers in Psychology, 2024)
This study investigates soccer referees' decision-making (DM) processes concerning the issuance of yellow cards in response to fouls. 60 male participants, categorized into expert (n=30) and novice (n=30) groups based on their refereeing experience and qualifications, participated in a 2×2×2 mixed-design experiment. The independent variables included Decision-Making Style (DMS: Analytical Decision-Making [ADM] vs. Intuitive Decision-Making [IDM]), Video Type (yellow card foul vs. non-yellow card foul), and Referee Level (expert vs. novice). The dependent variables included accuracy rate (ACC), discrimination index (D), self-confidence index (C), and overconfidence index (OC). The results revealed a significant main effect of DMS, wherein ADM showed higher accuracy than IDM.Expert referees demonstrated a superior ACC compared to novice referees. Additionally, the interaction between DMS and Referee Level proved significant, highlighting variability in the effectiveness of ADM and IDM between expert and novice referees. Furthermore, the OC suggested that although both expert and novice referees demonstrated overconfidence, the degree was significantly higher in experts, particularly during IDM. These findings underscored the complexity of referees' DM in high-pressure situations and the potential benefits of ADM strategies. This study contributed to understanding cognitive biases in sports officiating and provided insights for training programs aimed at improving referee performance. The study found that while Automated Decision Making (ADM) helps novice referees make accurate decisions, expert referees are more prone to overconfidence, especially when relying on intuition. Targeted training is needed to improve performance and mitigate overconfidence in high-pressure situations. This study contributed to understanding cognitive biases in sports officiating and provided insights for training programs aimed at improving referee performance.